Mechanics of composite materials - Christensen, R. M. (Dover Civil and Mechanical Engineering Ser., 2005)
Graduate-level text assembles, interprets, and interrelates contributions tofield of composite materials from theoretical research, lab developments, and product applications. Focuses on continuum mechanics aspects of behavior; specifically, it invokes idealized geometric models of heterogeneous system fortheoretical predictions of macroscopic properties in terms of individual constituent materials. 1979 edition.